PENYULUHAN PENGENALAN DAGUSIBU OBAT PADA SISWA-SISWI SEKOLAH INDONESIA KUALA LUMPUR (SIKL) DI MALAYSIA - Himyatul Hidayah; Surya Amal; Dedy Frianto (Bajang Institute, 2025)
The inappropriate and irrational use of medicines is a public health issue that needs to be addressed early on. Students, as the next generation at risk of self-medication, need adequate medicine literacy. The DAGUSIBU (Obtain, Use, Store, and Dispose) program launched by the Indonesian Pharmacists Association and the Indonesian Ministry of Health is an important guide to the smart use of medicines. This community service activity aims to increase the knowledge and awareness of students at the Indonesian School in Kuala Lumpur (SIKL) about the DAGUSIBU principles so that they are able to use drugs safely and rationally. The activity was carried out using interactive counseling methods, question and answer sessions, and simulations, which began with a pre-test and ended with a post-test to measure the increase in knowledge. There was a significant increase in the average knowledge score of students after receiving education. The average pre-test score of 73.3% increased to 93.3% on the post-test. DAGUSIBU education was effective in improving SIKL students' understanding of proper and correct medication use, thereby supporting the creation of a generation that uses medication wisely in accordance with the Gema Cermat program